Hydrophobic nature and effects of culture conditions on biofilm formation by the cellulolytic actinomycete Thermobifida fusca - Almaris N. Alonso (AIMS Microbiology, 2015)
Thermobifida fusca produces a firmly attached biofilm on nutritive and non-nutritive surfaces, such as cellulose, glass, plastic, metal and Teflon®. The ability to bind to surfaces has been suggested as a competitive advantage for microbes in soil environments. Results of previous investigations indicated that a Gram-positive cellulolytic soil bacteria, Cellulomonas uda, a facultative aerobe, specifically adhered to nutritive surfaces forming biofilms, but cells did not colonize non-nutritive surfaces. Cell surface hydrophobicity has been implicated in the interactions between bacteria and the adhesion to surfaces. It was recently described that the cellulolytic actinomycete T. fusca cells hydrophobicity was measured and compared to the cellulolytic soil bacteria C. uda. Also, T. fusca biofilm formation on non-nutritive surface, such as polyvinyl chloride, was examined by testing various culture ingredients to determine a possible trigger mechanism for biofilm formation. Experimental results showed that partitioning of bacterial cells to various hydrocarbons was higher in T. fusca cells than in C. uda. The results of this study suggest that the attachment to multiple surfaces by T. fusca could depend on nutrient availability, pH, salt concentrations, and the higher hydrophobic nature of bacterial cells. Possibly, these characteristics may confer T. fusca a selective advantage to compete and survive among the many environments it thrives.